Knowledge assets and knowledge audits - Hand, Pawan; Pagani, Jean; Bedford, Denise (Working methods for knowledge management, 2019)
With the rising importance of knowledge as a primary factor in global industries, it is increasingly necessary for knowledge management professionals to understand, engage with, and speak the language of assets, investments and auditing. However, all too often, professionals don't have these skills, and have no way to learn them. This exciting guide helps knowledge management professionals gain a basic understanding of assets, investments and audits, so they can command respect from those who are in control of financial investments. It also ensures that organizations have a roadmap for developing short- and long-term investment strategies. Providing guidance for identifying assets - and liabilities - as well as describing the types of investment available to align with knowledge assets, expert authors Pawan Handa, Jean Pagani, and Denise Bedford walk readers through standard audit practices, and help you through the process of designing, conducting, and reporting on the results of a knowledge audit. For knowledge management professionals, corporate and business leaders and managers, workforce professionals, and educators, this is an unmissable guide that unites the new face of the global economy with accepted auditing practices.